Gli slavi dal punto di vista italiano – difficoltà traduttologiche nella traduzione de Gli slavi. Storia, cultura e lingue dalle origini ai nostri giorni di Marcello Garzaniti - Groblińska, Justyna; Kowalik, Katarzyna (Translatoryka i Translacje. Przekład w XXI wieku. Wyzwania – możliwości – trendy, 2020)
The article is an effect of cooperation of the authors in the translation of the Marcello Garzaniti’s monograph Gli slavi. Storia, cultura e lingue dalle origini ai nostri giorni from Italian into Polish. The translators classify, describe and analyze causes and effects of such phenomena as: different vocabulary of two languages, syntax transfer from Italian to Polish, lexical and stylistic unification of text elaborated by three different translators, material errors appearing in the source text, cases of obsolescence in the original version, scientific style, author’s idiolectal expressions, development of knowledge in the translation process, Polish culture’s perception in Italy and its influence on translator’s decisions. The discussed issues represent a synthesis of problems with which a translator from Italian into Polish can face.